The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s12192-017-0768-y
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant heat shock protein 27 (HSP27/HSPB1) protects against cadmium-induced oxidative stress and toxicity in human cervical cancer cells

Abstract: Cadmium (Cd) is a carcinogen with several well-described toxicological effects in humans, but its molecular mechanisms are still not fully understood. Overexpression of heat shock protein 27 (HSP27/HSPB1)-a multifunctional protein chaperone-has been shown to protect cells from oxidative damage and apoptosis triggered by Cd exposure. The aims of this work were to investigate the potential use of extracellular recombinant HSP27 to prevent/counteract Cd-induced cellular toxicity and to evaluate if peroxynitrite w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 90 publications
0
19
0
Order By: Relevance
“…It is estimated that approximately over 500,000 new cases are reported each year (1). Previous studies have indicated that human papilloma virus (HPV) infection is the major cause of cervical cancer (2,3). Undoubtedly, long term exposure to oxidative stress by cervical epithelial tissues will lead to the persistent, chronic viral infections, thereby causing genetic rearrangements and genomic instability due to the integration of the viral genome (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that approximately over 500,000 new cases are reported each year (1). Previous studies have indicated that human papilloma virus (HPV) infection is the major cause of cervical cancer (2,3). Undoubtedly, long term exposure to oxidative stress by cervical epithelial tissues will lead to the persistent, chronic viral infections, thereby causing genetic rearrangements and genomic instability due to the integration of the viral genome (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…At present, it is the staple food of more than half the world’s population (Wang et al, 2013). Cd is carcinogenic to humans and has been classified as a Class I carcinogen by the International Agency for Research on Cancer (Broerse et al, 2012; Alvarez-Olmedo et al, 2017). Cd is mainly absorbed from the soil through the roots and reaches the vascular bundle through the two plant transport pathways—the symplast and the apoplast—by which it is then transported to the stems and leaves and later migrates to the grains, finally accumulating in the human body through the food chain, thereby causing serious harm to human health (Yao et al, 2003; Seregin and Kozhevnikova, 2008; Yoneyama et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock protein 27 (Hsp27) is a member of the heat shock protein family which has been linked to tumor progression and, most interestingly, to chemotherapy resistance in cancer patients. There is evidence showing a role for Hsp27 in the balance between tumor dormancy and tumor progression, mediated by tumor-vascular interactions [ 4 ]. Hsp27 function is associated with deleterious outcomes in cancer and is associated with the development of drug resistance [ 5 ].…”
Section: Discussionmentioning
confidence: 99%